ИККИНЧИ ТАРТИБЛИ ОДДИЙ ДИФФЕРЕНЦИАЛ ТЕНГЛАМА УЧУН БИЦАДЗЕ-САМАРСКИЙ ВА БИРИНЧИ ТУР ИНТЕГРАЛ ШАРТЛИ МАСАЛА (Scientific journal of the Fergana State University, 2023)
In the paper, a problem with  Bitsadze-Samarski  condition  and first-type integral condition  for the second order ordinary differential equation is studied.